PENGARUH TIPE AGROEKOSISTEM TERHADAP PRODUKTIVITAS DAN KEBERLANJUTAN USAHATANI KOPI - Rusdi Evizal; Tohari Tohari; Irfan D. Prijambada; Jaka Widada; F. E. Prasmatiwi; Afandi Afandi (JURNAL AGROTROPIKA, 2010)
Shade trees provide ecological benefits such as soil conservation, biodiversity conservation, and providing nutrient through litter fall and nitrogen fixation by legume trees. Therefore, shade tree is a key factor for sustainability coffee production. To evaluate productivity and sustainability of coffee agroecosystems a study was conducted at Sumberjaya Sub-district, West Lampung, Indonesia, during 2007-2010. Farmers were interviewed and two plots of Coffea canephora were set. Plot I was a long term experimental plot, established from shrub to young coffee agro-ecosystems with treatments of open-grown (sun) coffee and Gliricidae sepium, Erythrina indica and Michelia champaca shaded-grown coffee. Plot II was mature coffee fields of 15 years old with the same types of shade trees. The results showed that tipe of coffee agro-ecosystems determined productivity which legume-shaded coffee were higher than nonlegume-shade coffee or sun coffee. Based on the value of Sustainable Yield Index, Benefit Cost Ratio, Net Present Value, and Internal Rate of Return, Gliricidae sepium and Erythrina indica shaded coffee were more visible therefore more sustainable than 2 others coffee agro-ecosystems. Based on the survey and experimental plot, productivity of coffee agro-ecosystems of 3-26 yeras old showed two maximum points resulted in a regression of polinomial model. Key words: coffee, shade tree, productivity, sustainability